Evolution Of Geopolitic Factors, Determining Regional Spatial Planning Of Arctic Regions - Valery B. Mitko; Vladimir A. Shitinskiy; Marina V. Minina (European Regional Science Association (ERSA), 2013)
Purpose of one of the priority projects of the Arctic academy of sciences is development, based on the principles of safe and sustainable development, taking into account the experience of United Nations - HABITAT and purposes of the development of United Nations, practical recommendations regarding the guarantee of level and quality of the life of population and sustainable development of the populated areas of Russia, the creation on the basis of the development of the contemporary engineering and transport infrastructure of favorable conditions for the effective economic activity, the economical utilization of natural resources, protection of environment with the use of a contemporary system of local self-guidance to in connection with selected pilot city- models. This purpose determines the basic content of the spatial planning of Arctic regions.The special features of the geopolitical factors, which determine interregional interactions of the Arctic super-region consist in the new role of regions under the conditions of globalization. In the presentation there are geographical, political, economical, ecological, military, demographic, cultural-religious, ethnic,intellectual factors discussion. Geographical factor is defined by spatial position and natural resources. It is basic for Russia and its evolution only for the last century had an essential change of Russia and new approaches of definiting of external borders of continental shelf in Arctic regions instead of sectorial to the following from the Convention on the International marine law accepted not by all subarctic states. Political factor consists in type of statehood, organizational structure of management, division of authorities, social structure of a society, presence of a civil society, freedom of the Mass Media.Economic factor is defined by people standard of living, capacities, agrarian capacities, a transport communication infrastructure, mobilization capacities. This factor is the major, defining the maintenance and forms the inter-regional and intraregional interaction. The comment can be only one as there are interesting slogans of type «Fights for Arctic regions» which are however not unreasonable, but evolution of this factor allows to assert that the one who will provide higher quality of life in region will win fight. Here one more important thesis is pertinent: if quality of life grows in region more slowly than manufacture growth there will be colonial character of interactions.Russia has made enormous efforts in North development. Unique manufactures in the north, unique Northern sea route are created. Now all leading countries show heightened interest to Arctic regions as to a source of safe development in the XXI century. Actual are questions: What is mission of Russia in Arctic? Has Russia abilities to discharge such mission? Are other States agree and approve Russian mission in Arctic?
Keywords: 330; geopolitical; evolution; factors; economic; regional; cooperation; demography; ecological; sustainable; development; policy; cultural-religious; ethnic; intellectual; intraregional; interaction; spatial